Bài 1:
a) 22 : (1 - x) = -11
=> 1 - x = 22 : (-11) = -2
=> x = 1 - (-2) = 3
b) x - 14 = 3x + 18
=> x - 3x = 18 + 14
=> x - 3x = 32
=> (-2). x = 32
=> x = 32 : (-2) = -16
c) -185 - 5(x - 5) = 5 . 42
=> -185 - 5(x - 5) = 5 . 16 = 80
=> 5(x - 5) = -185 - 80 = (-185) + (-80) = -265
=> x - 5 = -265 : 5 = -53
=> x = -53 + 5 = -48
d) 4(x + 2)3 - 7 = 101
=> 4(x + 2)3 = 101 + 7 = 108
=> (x + 2)3 = 108 : 4 = 27
=> x + 2 = 3
=> x = 3 - 2 = 1
e) 11 - |x - 6| = (-3)2
=> 11 - |x - 6| = 9
=> |x - 6| = 11 - 9 = 2
=> \(\left[{}\begin{matrix}x-6=2\\x-6=-2\end{matrix}\right.\)
=> \(\left[{}\begin{matrix}x=2+6=8\\x=-2+6=4\end{matrix}\right.\)
Vậy:..............
f/ (x - 2)(5 - x) = 0
=> \(\left[{}\begin{matrix}x-2=0\\5-x=0\end{matrix}\right.\)
=> \(\left[{}\begin{matrix}x=0+2=2\\x=5-0=5\end{matrix}\right.\)
Vậy:.........
Cảm ơn bạn nhiù nha